2017
DOI: 10.1371/journal.pone.0179100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of benzazole compounds that induce HIV-1 transcription

Abstract: Despite advances in antiretroviral therapy, HIV-1 infection remains incurable in patients and continues to present a significant public health burden worldwide. While a number of factors contribute to persistent HIV-1 infection in patients, the presence of a stable, long-lived reservoir of latent provirus represents a significant hurdle in realizing an effective cure. One potential strategy to eliminate HIV-1 reservoirs in patients is reactivation of latent provirus with latency reversing agents in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…They were not HDACIs and the HIV-1 transcription was driven neither by the NF-κB signaling pathway nor by stimulating of HIV-1 LTR. These data indicated that benzazole might be a promising chemotype to be developed into potent LRAs with appropriate chemical optimizations and further investigation into the mechanism of actions [128].…”
Section: Benzazole Derivativementioning
confidence: 97%
“…They were not HDACIs and the HIV-1 transcription was driven neither by the NF-κB signaling pathway nor by stimulating of HIV-1 LTR. These data indicated that benzazole might be a promising chemotype to be developed into potent LRAs with appropriate chemical optimizations and further investigation into the mechanism of actions [128].…”
Section: Benzazole Derivativementioning
confidence: 97%
“…Cytokines/receptor agonists IL IL-2, IL-7, IL-15 [31] TCR/Co-receptor activators Maraviroc [32] TLR agonists TLR2, 3, 7, 8, 9 agonists [33] Epigenetic modifiers HDAC inhibitors Vorinistat, panobinostat, AR-42, MS-275, chidamide HDAC1, 2, 3 [34][35][36][37][38] Histone methyltransferase inhibitors Chaetocin, AZ505 Suv39H1, SMYD2 [39,40] Intracellular signaling modulators PKC agonists Ingenol EK-16A, gnidimacrin, bryostatin, SUW133, PEP005/Inge-nol-3angelate, Prostratin, Bryostatin-1, IDB NF-kappaB [41][42][43] AMPK activators Dibutyryl-cAMP [44] JAK/STAT agonists Benzotriazole, benzazole STAT3 [45,46] IAP agonists Debio1143 NF-kappaB (non-canonical) [47] Transcriptional elongation regulators BET inhibitors JQ1, MMQO, UMB-136, RVX-208, PFI-1, OTX015…”
Section: Referencesmentioning
confidence: 99%
“…Therefore, these compounds have been widely studied in diverse areas of chemistry. Some of important pharmacological activities of these heterocycles include of being anticancer, [ 1 ] antitumor, [ 2 ] anticonvulsant, [ 3 ] anti‐Parkinson, [ 4 ] anti‐Alzheimer, [ 5 ] anti‐HIV, [ 6 ] anti‐helminthic, [ 7 ] antifungal, [ 8 ] antibacterial, [ 9 ] antimicrobial, [ 10 ] antiviral, [ 11 ] and antihistaminic. [ 12 ] Because of such attractive applications, many studies have focused on the development of new synthetic benzazoles methodologies.…”
Section: Introductionmentioning
confidence: 99%